Strengthening emotional intelligence intervention on behavior changes of mothers in stunting prevention - Sari, Rita Kartika; Mayangsari, Citra Primavita; Mashoedi, Imam Djamaluddin; Intan, Yulice Soraya Nur; Trisnadi, Setyo; Aprilyanti, Dwi Fikha (International Journal of Public Health Science (IJPHS), 2024)
This study aimed to determine the effect of applying Emotional intelligence reinforcement to changes in stunting prevention behavior at the Kedung 2 Health Center, Jepara. This study employed a cross-sectional approach and data from participants at the Kedung 2 Public Health Center in Jepara. Public Health Center, Jepara. Participants were taken by purposive sampling according to predetermined maternal criteria, and 82 participants were obtained. Quasi-experimental research methods with two groups of emotional intelligence strengthening design, pre-intervention and post-intervention. Data collection used a questionnaire to measure the emotional intelligence of respondents and stunting prevention behavior. The data were then analyzed using the SPSS program. The correlation value shows that there is a strong relationship between the strengthening of emotional intelligence interventions and changes in maternal stunting prevention behavior, with a correlation value of 0.905 and a significance value of less than 0.001. The results of the T-test also showed significant behavioral changes in stunting prevention behavior before and after the application of strengthening emotional intelligence, with a significance value of 0.008. Strengthening emotional intelligence has a strong positive correlation with stunting prevention behavior, and the results of the T-test show that there is a significant effect on the results of stunting prevention behavior between before and after strengthening emotional intelligence. As a result, strengthening maternal emotional intelligence should be a priority to prevent stunting.